2021
DOI: 10.1101/2021.01.08.425915
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ad26.COV2.S-elicited immunity protects against G614 spike variant SARS-CoV-2 infection in Syrian hamsters and does not enhance respiratory disease in challenged animals with breakthrough infection after sub-optimal vaccine dosing

Abstract: Previously we have shown that a single dose of recombinant adenovirus serotype 26 (Ad26) vaccine expressing a prefusion stabilized SARS-CoV-2 spike antigen (Ad26.COV2.S) is immunogenic and provides protection in Syrian hamster and non-human primate SARS-CoV-2 infection models. Here, we investigated the immunogenicity, protective efficacy and potential for vaccine-associated enhanced respiratory disease (VAERD) mediated by Ad26.COV2.S in a moderate disease Syrian hamster challenge model, using the currently mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…In the present study, the safety and immunogenicity of three adenovirus-based vaccine candidates, including the prime-only, prime-boost, and heterologous prime-boost vaccines, were examined in mice, rabbits, and hamsters. The mouse and rabbit models, as convenient immunogenicity models, along with hamsters, as suitable viral challenge models, have been used in many studies [17] , [18] . In line with previous research on adenovector-based vaccines, no vaccine-induced side effects were observed in the brain, lung, kidney, or liver tissues of vaccinated animals compared to the mock [18] , [19] .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the safety and immunogenicity of three adenovirus-based vaccine candidates, including the prime-only, prime-boost, and heterologous prime-boost vaccines, were examined in mice, rabbits, and hamsters. The mouse and rabbit models, as convenient immunogenicity models, along with hamsters, as suitable viral challenge models, have been used in many studies [17] , [18] . In line with previous research on adenovector-based vaccines, no vaccine-induced side effects were observed in the brain, lung, kidney, or liver tissues of vaccinated animals compared to the mock [18] , [19] .…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the vaccine is still in clinical trials. The study showed the vaccine to be effective, and no adverse effects were observed in the study [23].…”
Section: Resultsmentioning
confidence: 81%
“…The authors also created a spike protein bearing all eight mutations seen within the B.1.1.7 variant and found that 10 out of 15 participants showed lowered Efficacy against it. Overall the authors found the vaccine effective against the B.1.1.7 variant, although to a lesser degree, and immunogenicity appears to drop the older the subject becomes [24].…”
Section: Resultsmentioning
confidence: 93%
“…It is a recombinant adenovirus serotype 26 vector encoding SARS-CoV-2 peplomers based on SARS-CoV-2 Wuhan-Hu-1 isolate strain (Genbank accession number: MN908947) [ 135 ]. Ad26.COV2 demonstrated high efficacy under preclinical setting in multiple animal models, including Syrian hamster, non-human primates, in which all vaccinated animals showed a rapid increase in neutralizing antibodies and reduction in lung viral load [ 136 , 137 , 138 , 139 ]. Notably, all animal models reported the absence of any adverse side effects or signs of vaccine-related respiratory disease, suggestive of a safe and tolerable vaccine candidate against SARS-CoV-2 [ 136 , 137 , 138 , 139 ].…”
Section: Covid-19 Vaccine Developmentmentioning
confidence: 99%
“…Ad26.COV2 demonstrated high efficacy under preclinical setting in multiple animal models, including Syrian hamster, non-human primates, in which all vaccinated animals showed a rapid increase in neutralizing antibodies and reduction in lung viral load [ 136 , 137 , 138 , 139 ]. Notably, all animal models reported the absence of any adverse side effects or signs of vaccine-related respiratory disease, suggestive of a safe and tolerable vaccine candidate against SARS-CoV-2 [ 136 , 137 , 138 , 139 ]. Under clinical setting, safety and tolerability trial (NCT04436276) exhibited high safety and efficacy profile of Ad26.COV2 in human participants, with elevated neutralizing antibody response of 88% in the adult population (aged 18–55) and 93% in the elderly population (aged > 65) without any significant adverse events reported [ 140 ].…”
Section: Covid-19 Vaccine Developmentmentioning
confidence: 99%